2016
DOI: 10.1002/2015tc003840
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure of the Bighorn Mountains region: Precambrian influence on Laramide shortening and uplift in north‐central Wyoming

Abstract: The crustal structure of north-central Wyoming records a history of complex lithospheric evolution from Precambrian accretion to Cretaceous-Paleogene Laramide shortening. We present two active source P wave velocity model profiles collected as part of the Bighorn Arch Seismic Experiment in 2010. Analyses of these velocity models and single-fold reflection data, together with potential field modeling of regional gravity and magnetic signals, constrain crustal structure and thickness of the Bighorn region. We im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 84 publications
2
46
1
Order By: Relevance
“…The nature of these faults at greater depths is even more uncertain. Previous studies in the region have identified vertical seismic velocity gradient increases at ~25 km depth, thus defining a midcrustal transition zone (Gorman et al, 2002;Worthington, et al, 2016). This midcrustal transition has been identified at ~6.5 km/s and has been interpreted as either a crustal detachment surface (Erslev, 1993) or, where velocities exceed 7 km/s, a mafic underplate (Snelson et al, 1998;Gorman et al, 2002; see also Fig.…”
Section: Subsurface Relations and Two-dimensional Interpretationsmentioning
confidence: 84%
See 2 more Smart Citations
“…The nature of these faults at greater depths is even more uncertain. Previous studies in the region have identified vertical seismic velocity gradient increases at ~25 km depth, thus defining a midcrustal transition zone (Gorman et al, 2002;Worthington, et al, 2016). This midcrustal transition has been identified at ~6.5 km/s and has been interpreted as either a crustal detachment surface (Erslev, 1993) or, where velocities exceed 7 km/s, a mafic underplate (Snelson et al, 1998;Gorman et al, 2002; see also Fig.…”
Section: Subsurface Relations and Two-dimensional Interpretationsmentioning
confidence: 84%
“…The major thrusts are the thick-skinned, basement-involved, Laramide structures, with dips of 30°-45° at the surface (Smithson et al, 1979;Stone, 2003;Weil et al, 2016), and movement on these faults formed the prototypical Laramide arches of Wyoming. Subsurface studies have suggested that these structures may sole out into a midcrustal detachment zone at depths of ~25 km (Blackstone, 1990a;Erslev, 1993;Yeck et al, 2014;Worthington et al, 2016). However, the Consortium for Continental Reflection Profiling (COCORP) line across the southern Wind River thrust shows a relatively consistent apparent fault dip (38°) to ~25 km, below which the reflector disappears (Smithson et al, 1979).…”
Section: Nnw Arcuate Zonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Doublets are predominant in this area in Figure b, and SW Vs models show some of the highest velocities and thickest high‐velocity crust here. However, a recent refraction experiment in northern Wyoming (profile 44 in Figure a) suggests that high‐velocity lower crust is locally discontinuous in the region and apparently absent directly beneath the Bighorn Mountains [ Worthington et al ., ; Yeck et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the Precambrian development in this region are hindered by the lack of basement outcrops (with the exception of the Black Hills), lack of high resolution aeromagnetic and other geophysical data (for the Dakotas, in particular), and a lack of drill holes to basement across much of the area. Yet, underlying this region are significant basement terranes and tectonic boundaries, including the suture between the Wyoming and Superior cratons beneath the Dakotas (Dahl et al 2005;Worthington et al 2015;Kilian et al 2016), the southern terminus of the Trans-Hudson orogen, and the southwestern margin of the Superior craton (Figures 1, 2). The nature of these boundaries is of fundamental importance to unraveling the Precambrian evolution of the North American craton.…”
Section: Introductionmentioning
confidence: 99%